Turkish Religious Diplomacy An Analysis of Efforts to Achieve Socio-Political Consensus Through the 2016 Global Islamic Calendar Congress - Muhammad Arafat; Susiknan Azhari; Anisah Budiwati; Yusril Nurilham (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The absence of a universally accepted Hijri calendar has long generated socio-religious fragmentation across the Muslim world, with recurrent divergences over the start of Ramadan, Shawwal, and Dhu al-Hijjah. This article interprets the 2016 International Hijri Calendar Unity Congress in Istanbul not merely as a technical-astronomical gathering but as a strategic exercise in religious diplomacy orchestrated by Turkey’s Presidency of Religious Affairs (Diyanet). Using a descriptive–analytical qualitative design, the study synthesizes academic, institutional, and media sources to examine how Turkey leveraged agenda-setting, coalition-building, and procedural innovation to advance calendar unification. Historically embedded within a longer OIC-linked process (2005 Yemen resolutions; 2008 Mecca; 2013 Istanbul), the 2016 congress converted protracted deliberation into a vote-backed, criteria-specific decision package. Subsequent diffusion (most clearly the SGHC adoption by Muhammadiyah for full implementation from 26 June 2025) demonstrates Turkey’s capacity to translate scientific-fiqh convergence into transnational policy uptake. Findings indicate that the congress projected Turkey as a modern, rational leader capable of reframing a civilizational problem while subtly contesting traditional Arab religious authorities. Yet universal consensus remains elusive due to sovereignty politics (notably in Saudi Arabia), OIC institutional inertia, and grassroots attachment to local rukyat. The article clarifies both the reach and the limits of Turkey’s faith-based soft power in a polycentric Islamic order.